Factors Affecting the Gender Difference in Dream Sharing Frequency. (March 2015) - Schredl, Michael; Kim, Eugenia; Labudek, Sarah; Schädler, Anna; Göritz, Anja S.
Numerous studies have shown that women tend to share dreams more often than men. However, research looking at factors that might explain this gender difference is scarce. The present online study ( N = 1, 808) clearly showed that gender differences in frequency of sharing emotional experiences and sex role orientation (femininity/expressivity) did affect the gender difference in dream sharing whereas dream-related variables such as dream recall frequency and attitude towards dreams did not. Many of the factors associated with dream sharing indicate that the socialization processes might have an effect on dream variables in adulthood. To pursue this line of research, it would be fruitful to study dream sharing within the family.